Evaluation of the effect of the synthesis method on the performance of manganese spinel as cathode material in lithium-ion batteries - Uribe Grajales, Lina Maria (2018)
Spinel-structured lithium manganese oxide (LiMn2O4) has been successfully used as a cathode material for various lithium batteries. To improve the capacity and increase the discharge potential of the battery, transition metals are commonly added to the spinel as dopants or as a substitute for manganese. This can also confer stability on the structure of the cathode material. In this work, the production and performance of spinel LiMn2O4 (LMO) and LiNi0:5Mn1:5O4 (LNMO) by solid-state and sol-gel synthesis methods were studied. Synthetized (LMO) and (LNMO) materials were characterized by Raman spectroscopy and X-ray diffraction (XRD) to verify the formation of a spinel-like structure. It was corroborated that both synthesis methods can produce an adequate spinel structure. SEM analyses showed that in general, spinel take an octahedral form. The particle size changes according to the synthesis method used. Lower particle sizes were obtained by sol-gel. The electrochemical characterization demonstrates that solid-state synthesis generates compounds with greater purity and crystallinity, which induces a greater capacity of lithium ion intercalation. The addition of nickel to the spinel increases the discharge potential of the cathode by 0.5V.